Experimental assessment of the ultimate performance and lateral drift behaviour of precast concrete building cores. Issue 12 (September 2020) - Menegon, Scott J; Wilson, John L; Lam, Nelson TK; Gad, Emad F
Precast concrete building cores are a widely used lateral load resisting system in low and mid-rise multi-storey buildings. However, despite their widespread use in countries like Australia or New Zealand, a very little research or experimental testing has been undertaken to assess their lateral drift behaviour. This article will present the findings and observations of a recent experimental testing programme into reinforced concrete precast building cores, which included three large-scale 'box-shaped' precast building core specimens. Adjacent panels in each specimen were connected together using welded stitch plate connections and then connected to foundation blocks on the top and bottom using grout tube connections. The results of the testing showed that the welded stitch plate connections were too flexible to allow full composite action to be developed in the cross-section, which meant the precast building core specimens were around 25% more flexible than an equivalent cast in-situ version. The testing also highlighted common detailing and construction deficiencies that can severely inhibit the ductility of the core.